Kajian Potensi Daya Tarik Wisata Heritage di Indonesia - Damayanti, Rima Ayu; Puspitasari, Ardiana Yuli (Universitas Islam Sultan Agung, 2024)
ABSTRACTIndonesia, known as a pluralistic country, has diverse forms of cultural expression including tangible culture and intangible culture. Both of these are important factors in attracting tourists to travel to a tourist area, in particular, heritage tourism. Attraction can be defined as something that has the potential to be used as a tourist attraction because it has unique characteristics to attract someone to visit a heritage tourist destination in the form of historical buildings, cultural attractions, customs and ways of life. The author is interested in studying the correlation between heritage tourism attractions and tourist attractions that aim to explore the potential of an area so that the welfare of tourists and local communities can experience an increase due to the optimal quality of attraction management. The method used is a descriptive approach and literature review both sourced from articles and journals that have to do with the study of heritage tourist attractions in Indonesia. The results of the discussion show that tourist interest when visiting tourist attractions is influenced by 3 aspects, namely something to see, something to do, and something to buy. First, something to see includes the uniqueness of cultural heritage buildings not only because of their age, but also because of their history, such as Borobudur Temple, GWK Statue, and historical buildings in Tangerang City and Semarang Old Town. In addition, something to see can be in the form of annual festivals/events and cultural exhibitions, for example the old city festival; Second, something to do, namely in the form of tour packages in the form of a program to explore the heritage area management body or photo hunting in heritage tourism; Third, something to buy in the form of souvenirs to special foods, including handicrafts and processed regional specialties. The management of the heritage tourism potential of an area is still found to have various shortcomings so that practical solutions are needed to improve it which aims to improve the quality of potential tourist attractions that present the image and identity of the tourist area as a heritage tourist attraction.Keywords: Attraction; Tourism Attraction; Potential; Heritage Tourism ABSTRAKIndonesia yang dikenal sebagai negara majemuk mempunyai bentuk ekspresi budaya yang beragam meliputi budaya benda (tangible culture) dan budaya tak benda (intangible culture). Kedua hal tersebut menjadi faktor penting dalam menarik wisatawan untuk melakukan wisata ke suatu daerah wisata, khususnya, wisata heritage. Atraksi dapat didefinisikan sebagai sesuatu yang berpotensi dijadikan daya tarik wisata karena mempunyai sifat unik guna menarik seseorang untuk berkunjung ke suatu daerah tujuan wisata heritage baik berupa, bangunan bersejarah, atraksi budaya, adat istiadat maupun cara hidup masyarakat. Penulis tertarik untuk mengkaji terkait dengan korelasi antara daya tarik wisata heritage dengan atraksi wisata yang bertujuan menggali potensi suatu daerah sehingga kesejahteraan wisatawan maupun masyarakat lokal dapat mengalami peningkatkan karena kualitas pengelolaan atraksi yang optimal. Metode yang digunakan yaitu dengan pendekatan deskriptif dan literatur review baik bersumber dari artikel dan jurnal yang terdapat kaitannya dengan kajian atraksi daya tarik wisata heritage di Indonesia. Hasil pembahasan menunjukkan bahwa minat wisatawan ketika berkunjung pada daya tarik wisata dipengaruhi oleh 3 aspek, yaitu something to see, something to do, serta something to buy. Pertama, something to see meliputi keunikan bangunan cagar budaya bukan hanya karena usianya, tetapi juga karena sejarahnya, seperti Candi Borobudur, Patung GWK, dan bangunan bersejarah di Kota Tangerang dan Kota Lama Semarang. Selain itu, something to see dapat berupa festival/event tahunan serta pameran budaya contohnya festival kota lama; Kedua, something to do yakni berupa paket tour berupa program menjelajah badan pengelola kawasan heritage ataupun hunting foto di wisata heritage ; Ketiga something to buy berupa cinderamata hingga makanan khas, diantaranya kerajinan tangan maupun olahan makanan khas daerah. Pengelolaan potensi pariwisata heritage suatu daerah masih ditemukan berbagai kekurangan sehingga diperlukan solusi praktis untuk memperbaikinya yang bertujuan untuk meningkatkan kualitas potensi daya tarik wisata yang mempresentasikan citra dan identitas kawasan wisata sebagai obyek wisata heritage.Kata Kunci: Atraksi; Daya Tarik Wisata; Potensi; Wisata Heritage